Copy number variations (CNVs) and karyotyping analysis in males with azoospermia and oligospermia - Xing Xin; Peng Xu; Nan Wang; Yi Jiang; Jiaqiao Zhang; Shufang Li; Ying Zhu; Cong Zhang; Long Zhang; Hailong Huang; Ling Feng; Shaoshuai Wang (BMC Medical Genomics, 2023)
Abstract Background Considering the essential roles that genetic factors play in azoospermia and oligospermia, this study aims to identify abnormal chromosomes using karyotyping and CNVs and elucidate the associated genes in patients. Methods A total of 1157 azoospermia and oligospermia patients were recruited, of whom, 769 and 674 underwent next-generation sequencing (NGS) to identify CNVs and routine G-band karyotyping, respectively. Results First, 286 patients were co-analyzed using CNV sequencing (CNV-seq) and karyotyping. Of the 725 and 432 patients with azoospermia and oligospermia, 33.8% and 48.9% had abnormal karyotypes and CNVs, respectively. In particular, 47,XXY accounted for 44.18% and 26.33% of abnormal karyotypes and CNVs, respectively, representing the most frequent genetic aberration in azoospermia and oligospermia patients. Nevertheless, big Y and small Y accounted for 7.46% and 16.67% of abnormal karyotypes, respectively. We also identified high-frequency CNVs-loci, such as Xp22.31 and 2p24.3, in azoospermia and oligospermia patients. Conclusion Sex chromosome and autosomal CNV loci, such as Xp22.31 and 2p24.3, as well as the associated genes, such as VCX and NACAP9, could be candidate spermatogenesis genes. The high-frequency abnormal karyotypes, CNV loci, and hot genes represent new targets for future research.